Local rice farmers attitude and behavior towards agricultural programs and policies - Prasetyo, Hendro; Karmiyati, Diah; Hendroko Setyobudi, Roy; Fauzi, Ahmad; Pakarti, Trias Agung; Sri Susanti, Mardiana; Ali Khan, Waris; Neimane, Leila; Mel, Maizirwan (Pakistan Agricultural Research Council, 2022)
The government has been launching agricultural programs by producing rice of certain superior cultivars to achieve rice self-sufficiency and sustainability and bundling them with beneficial policies. However, quite a large number of rice farmers continue to grow local rice variants. This study aims to identify, analyze, and describe farmers’ attitude and behavior. A survey was employed for quantitative data gathering and an interview was for the qualitative ones. A total of 52 respondents were of local rice farmers in Sidodadi and Banturejo villages of Ngantang district, Malang Regency, East Java, Indonesia. The result of correlation test showed good cognitive, affective, and conative aspects of the farmers despite low achievement rates in all government programs. Social stratification significantly affected the farmers’ response on the programs. The farmers’ cognitive, affective, and educational aspects are also significantly influential in their response. Further motives are of internal factors (social) and external ones (official, organizational, private, cultural, and natural).